Exploring Students’ Attitudes in Learning English as a Foreign Language - Afrilina, Ananda Muddrika Zahara; Elfrida, Elfrida; Saputra, Dwi Bayu (Journal of English Education and Teaching, 2025)
This study investigated the attitudes of eighth-grade students at SMP Negeri 13 Kota Bengkulu towards learning English as a foreign language. This study aimed to determine students' attitudes towards learning English as a foreign language, specifically whether they hold positive or negative views. A mixed method was used in this study to uncover students' attitudes, which focuses on combining quantitative and qualitative approaches. To gather data, a carefully and systematically designed questionnaire was adopted, consisting of 30 questions using a five-point Likert scale survey. 60 participants were asked to answer a questionnaire. Irn addirtiron, ther irnterrvirerw was applirerd to obtairn a morer irn-derpth analysirs and 15 students were selected to be interviewed to support the responses to the questionnaire given. Three aspects of attitude being explored are: behavioural, cognitive and emotional. Most students showed positive attitudes towards learning English as a foreign language. Based on the three aspects above, from a behavioural aspect, it is evident that most students exhibit good behaviour in learning English. From the cognitive aspect, students have confidence, awareness, and knowledge in learning English. And also from the emotional aspect, students show that almost all students have good emotional attitudes toward learning English. The results of data analysis show that students are motivated and have positive attitudes in the three aspects of attitude. In the sense that their attitudes seem to influence their understanding, their participation, and their interest in the perceived benefits of learning English, as well as their strategies to improve their abilities.